EA-CRP: A Novel Energy-aware Clustering and Routing Protocol in Wireless Sensor Networks. (November 2018) - Darabkh, Khalid A.; Al-Maaitah, Noor J.; Jafar, Iyad F.; Khalifeh, Ala' F.
Abstract: This paper proposes a novel energy-aware and layering-based clustering and routing protocol (EA-CRP) for gathering data in WSNs. The main goal of EA-CRP is to reduce the energy consumption among all sensor nodes in the network. To achieve this goal, EA-CRP employs an innovative multilayered architecture. More specifically, we divide the field into a number of layers where the width of a layer not only decreases towards the base station, but also is composed of a certain number of clusters (sub layers). The proposed design not only shortens the communication distance between nodes, but also decreases the amount of communication overhead required for setting up clusters. Furthermore, a multi-hop routing algorithm for inter-cluster communications is proposed which basically considers the tradeoff between distance and the energy of relaying nodes. The effectiveness of EA-CRP is verified through comparing its results with those obtained from previous relevant protocols. Interestingly, our experimental results show that EA-CRP has superior performance in term of network lifetime, energy efficiency, and scalability.